An appraisal of theological training for untrained church leaders in Sub Saharan Africa : with particular reference to the training program of Veritas College - Wiid, Willem Jacobus (Stellenbosch : Stellenbosch University, 2012)
Thesis (DTh)--Stellenbosch University, 2002.